THE ROLE OF INTEGRATED CADASTRE DATABASE IN DISASTER RISK MANAGEMENT - Kusmiarto Kusmiarto (BHUMI: Jurnal Agraria dan Pertanahan, 2013)
Due to the complexity of the natural disaster in Indonesia, the effective disaster risk management should havecomprehensive information. Cadastre database using parcels as basic mapping units constitute the detailed information relatedto elements at risk. It is not easy for the institutions in charge with those disaster risk management to access the detailedinformation. The research is aimed at overcoming the above problems that is by designing the integrated cadastre databasescheme. The survey results are use to test the geo-database cadastre scheme. The evaluation is done by in depth interview tothe potential users. The result of evaluation showed that the cadastre database made is good enough to solve the abovementioned problems.Keywords: cadastre, design, geo-database, elements at risk, earthquake.